IMPLEMENTATION OF BAHASA INDONESIA AND LITERATURE CURRICULUM BASED ON LOCAL WISDOM - Sitorus, Friska Ria; ., Nurdiana; ., Syamsirudin; ., Salihin (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
Students, teachers, and curricula complement each other, which needs collaboration and interaction among those parties to reach an effective and holistic learning environment. Many factors influence curriculum development: local culture, diversity, and social conditions in an area. As Indonesian citizens, we should still be proud of the cultural diversity that our country has. Therefore, considering how foreign cultural values have developed rapidly, many schools, especially teachers, apply a learning curriculum based on local wisdom. This research aims to determine how the local wisdom-based curriculum is applied in Bahasa Indonesian and Literature lessons. This study uses the observation method, in which the data collection is based on what is observed and reviewed. At the junior high school, which was the object of the study, the researchers found several forms of local wisdom application in learning Indonesian. This application form is seen in the extracurricular, co-curricular, and extracurricular learning processes.